Editorial - Özerk, Kamil (International Electronic Journal of Elementary Education, 2026)
Dear IEJEE Readers, As Editor-in-Chief of the International Electronic Journal of Elementary Education (IEJEE), I am pleased to present this special issue on translanguaging. Translanguaging is a relatively recent and influential movement in the fields of second and foreign language education, bilingual education, and English-medium instruction worldwide. Given the breadth and complexity of this area, it is challenging to address all dimensions of translanguaging within a single issue. In this special issue, researchers explore diverse approaches to translanguaging pedagogy in migrant, bilingual, and refugee education across a range of educational contexts and countries. Together, these contributions offer valuable perspectives on theory, practice, and policy related to translanguaging in contemporary education. IEJEE has been published as an international electronic journal since 2008 and, over the past eighteen years, has successfully produced several special issues on timely and relevant topics. Unfortunately, this special issue encountered unforeseen challenges that delayed its publication. In April 2024, I began working with Dr. Khánh Lê (Queens College, CUNY) and Dr. Zhongfeng Tian (Rutgers University–Newark), who kindly agreed to serve as guest editors for this issue. Our collaboration proceeded smoothly for some time; however, in fall 2025, difficulties arose that ultimately prevented them from continuing in this role. After several extensions of deadlines, we were informed that they could no longer serve as special issue editors, and all submitted manuscripts were returned to the journal. The IEJEE editorial board and staff decided to continue the process rather than discontinue the issue. With informed consent from the authors, we proceeded to publish this special issue with eight articles. We sincerely thank Dr. Lê and Dr. Tian for their contributions during the earlier stages of the project, as well as the authors for their patience and commitment. We hope that this special issue will make a meaningful contribution to the field of translanguaging and to educational research more broadly. Sincerely, Dr. Kamil Özerk Editor-in-Chief, IEJEE